(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the cardiovascular-metabolic health profile and body composition of patients attending family medicine clinics, and to introduce preliminary experiences regarding the application of a self-service medical Kiosk in primary care settings. Methods: A cross-sectional study was conducted at three family medicine clinics from March to May 2025. Participants aged ≥14 years underwent blood pressure and body composition assessment using a medical Kiosk equipped with bioelectrical impedance analysis (BIA). Results: Among 715 participants (mean age 50.9 ± 15.1; 60.1% female), significant gender differences were observed in muscle mass, fat composition, fluid distribution, and metabolic indices (p < 0.001). Increasing age was associated with higher blood pressure and visceral fat, and lower BMR and muscle mass. These findings were statistically significant and aligned with global literature. Conclusion: The study provides reference data on the cardiovascular-metabolic health profile in family practice. The integrated medical Kiosk demonstrates feasibility for simultaneous assessment of health parameters, suggesting its potential for enhancing chronic disease screening and prevention in the community.